E EFEKTIVITAS PIJAT OKSITOSIN DAN AROMATERAPI LAVENDER TERHADAP PRODUKSI ASI PADA IBU NIFAS: EFEKTIVITAS PIJAT OKSITOSIN DAN AROMATERAPI LAVENDER TERHADAP PRODUKSI ASI PADA IBU NIFAS - Yanti, Ariu Dewi; Yulianti, Indra (Jurnal EDUNursing, 2024)
Breast milk is the most ideal food for newborns up to 6 months because it contains essential nutrients for the growth and development of babies. Barriers to exclusive breastfeeding in newborns are often caused by breast milk that has not come out and lack of milk production. This is due to reduced stimulation of the hormones prolactin and the hormone oxytocin which play a very important role in producing breast milk. There are various ways to overcome this problem, one of which is with oxytocin massage and lavender aromatherapy. The purpose of this study was to learn more and prove the effectiveness of oxytocin massage and lavender aromatherapy to increase milk production. the research method used is a systematic review. the results obtained were 15 research articles that met the research criteria and stated that there was a significant effect between oxytocin massage and lavender aromatherapy on the smoothness or production of breast milk. Keywords: Oxytocin Massage; Lavender Aromatherapy; Breast milk production; Postpartum Mother